Flavor mixing in a Lee-type model - Nishi, C. C. [UNESP]; Guzzo, M. M. (American Physical Society (APS), 2008)
An exactly solvable quantum field theory (QFT) model of Lee type is constructed to study how neutrino flavor eigenstates are created through interactions and how the localization properties of neutrinos follows from the parent particle that decays. The two-particle states formed by the neutrino and the accompanying charged lepton can be calculated exactly as well as their creation probabilities. We can show that the coherent creation of neutrino flavor eigenstates follows from the common negligible contribution of neutrino masses to their creation probabilities. On the other hand, it is shown that it is not possible to associate a well-defined flavor to coherent superpositions of charged leptons. © 2008 The American Physical Society.